KEBIJAKAN HUKUM PIDANA DALAM PENANGGULANGAN PENGGUNAAN DOPING OLEH ATLET - Kusuma, Wimroh Putut Wijaya; Artina, Dessy; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Doping is the administration of drugs or ingredients orally or parastallyto an athlete with the aim of increasing unnatural precision. In the Republic ofKenya, imprisonment and fines are imposed on athletes who have been proven touse doping in sports competitions contained in the Act of Kenya Anti-Doping ActNumber 5 of 2016. While in Indonesia doping is regulated in Law Number 3 of2005 concerning the National Sports System and Government Regulation Number17 of 2007 concerning the Implementation of Sports Week and Championship,which clearly prohibits the use of doping in every sports competition. However,there is a void of norms in the rules to become a fundamental problem in lawenforcement in carrying out these rules. The purpose of writing this thesis is:First, to find out the regulation of the ban on doping by athletes in Indonesia.Second, to find out the ideal concept of criminal law policy in overcoming dopinguse by athletes in Indonesia.This type of research can be classified in the type of normative legalresearch, because in this study the authors conducted research by examininglibrary materials. The data sources used are secondary data consisting of primarylegal materials, secondary legal materials and tertiary legal materials, becausethe authors conduct research on the principles of law by utilizing descriptivemethods to provide an overview of the handling of doping use by athletes.From the results of the study it can be concluded, First, the regulation onthe prohibition of doping use in Indonesia is regulated in Law Number 3 of 2005concerning the National Sports System System and Government RegulationNumber 17 of 2007 concerning the Implementation of Sports Week andChampionship. Second, the ideal concept of criminal law policy in the effort toovercome the use of doping by athletes requires a criminal law policy by applyingseveral stages, namely the formulation (legislative) stage, application (judicative)stage and execution (executive) stage. In hopes of redesigning doping rules inIndonesia and so that athletes understand the doping dangers for health and thegovernment to impose criminal sanctions in doping laws as well as in Kenya.Keywords: Doping-Use-Athlete